(untitled) (Indian Journal of Animal Production and Management, 2018)
A study was carried out in 30 large White Yorkshire piglets to find out the effect of early and split weaning on carcass characteristics. Four weaning age groups, 56 days of conventional weaning age as group 1 (n=8), early weaning of entire litter at 28 days as group 2 (n=10), split weaned piglets with heavy litter weaned at 28 days as group 3 (n=6), weak litter left with sow up to 56 days as group 4 (n=6) were compared. By the end of study period, pigs were slaughtered and the carcass traits were studied that included dressing percentage and meat: bone ratio. The dressing percent was significantly lower in 2nd group of piglets (73.29±0.51) compared to 1st (78.14±0.91), 3rd (76.49±0.53) and 4th (77.91±0.25) group. However no significant difference in dressing percent was observed among 1st, 3rd and 4th group piglets. The meat: bone ratio was significantly higher in 3rd group of piglets (3.20±0.02) compared to 1st (3.07±0.06), 2nd (3.03±0.05) and 4th (2.80±0.05).